Policing Model in Building Synergy to Improve Papuan Welfare - Paulus Waterpauw, Paulus Waterpauw; Tangkudung, Audrey G.; Sugiharto, Agus (Jurnal Keamanan Nasional, 2020)
Papua is one of the regions in the eastern part of Indonesia. Papua has great wealth and potential, however, there are several conflicts that often occur in Papua. The Papua problem must be resolved through dialogue with local leaders in order to restore political confidence in joining Indonesia. The method used in this research is qualitative by means of interviews and focus group discussions (FGD). Meanwhile, the theory used in this research is conflict resolution theory and the concept of policing in dealing with this conflict. The result of this research is a model of policing to build synergy between the Police-Indonesian National Army, the Regional Government, and the Community that integrate to deal with conflicts that occur in Papua. With an approach through communication with the heart and conducting the discussion goes down directly to the community.